Sekolah menengah Teknik / Vokasional online registration and placement system / Rosiah Darus - Darus, Rosiah (2003)
In Malaysia, after the student passes their Penilaian Menengah Rendah examination, PMR, they are qualified to further their study to Sekolah Berasrama Penuh or Technical and Vocational School in Malaysia. Before entering this Technical and Vocational School, they have to buy the form from Technical and Vocational School. The main problem is sometimes the form had been sold out and the forms are not sold in other places. They also must queue to get the form. While in Ministry of Education, Government of Malaysia is still in the midst of processing data for the enrolment of students to the technical and vocational school through manual processes. Due to this problem above, this Sekolah Menengah Teknik / Vokasional Online Registration And Placement System is designed by utihsing the advantages of the World Wide Web (WWW) technology available, which is widely used elsewhere. The applicant can make their registration through the Internet. The main objective ofthis web-based system is to ease students in their registration as compared to the conventional process. It will save money, time and energy. Administrator of Bahagian Pendidikan Teknik Vokasional (BPTV) also will use this system either to checking applicant's minimum eligibility entrance condition technical and vocational school, calculate merit, place the applicant to the school relevant to its chosen course, adding relevant data and get reports. This system has been developed in such a way to expedite the data entry. The system developer has followed those phases as closely as possible in order to ensure the system fulfils its objectives as well as the user requirements.